Investigation of Cooling and Glycerol Effect on Biosensor Transducer - Grischenko, V. I.; Nardid, O. A.; Rozanova, K. D.; Schetinsky, M. I.; Mangasarov, D. O. (Problems of Cryobiology and Cryomedicine, 2003)
There have been developed the recommendations as for low temperature preservation of transducers: slow cooling with silicone protective layer or rapid one with a protective layer of epoxy lacquer after treatment of the surface with 25% glycerol solution.